COVID-19 impacts on sport governance and management: a global, critical realist perspective - Byers , T.; Gormley, K.-L.; Winand, M.; Anagnostopoulos, C.; Richard, R.; Digennaro, S. (Managing Sport and Leisure, 2021)
This commentary considers the impacts of COVID-19 on sport governance and management, given the global threat to sport services and organizations evident as a result of the disease since early 2020. To frame this analysis of the impacts and lessons to be learned, we use a Critical Realist (CR) perspective, which takes a multi-level view of reality and seeks to establish how and why something occurs in reality [Byers, T. (2013). Using critical realism: A new perspective on control of volunteers in sport clubs. European Sport Management Quarterly, 13(1), 5-31. https://doi.org/10.1080/16184742.2012.744765]. While the existing commentaries and emerging research on COVID19 have focused on a superficial level of reality (i.e. what stakeholder responses have been), a CR view encourages a more holistic account of what and why something happens. Specifically, this commentary contributes to the discussion of COVID-19 impacts focusing on sport governance, using a philosophy that encourages examination of what is happening in sport organizations, how different stakeholder`s perspectives and assessment of the legitimacy of COVID-19 may reveal underlying social structures and biases that help explain sport administrator`s responses and value systems. We hope this novel perspective on sport governance encourages readers to think of new ways of organizing and governing that is more inclusive of diversity (e.g. race, gender, disability) in sport.